2006
DOI: 10.1128/jcm.44.3.1145-1149.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effective Detection of Toxigenic Clostridium difficile by a Two-Step Algorithm Including Tests for Antigen and Cytotoxin

Abstract: We evaluated a two-step algorithm for detecting toxigenic Clostridium difficile: an enzyme immunoassay for glutamate dehydrogenase antigen (Ag-EIA) and then, for antigen-positive specimens, a concurrent cell culture cytotoxicity neutralization assay (CCNA). Antigen-negative results were >99% predictive of CCNA negativity. Because the Ag-EIA reduced cell culture workload by Ϸ75 to 80% and two-step testing was complete in <3 days, we decided that this algorithm would be effective. Over 6 months, our laboratories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(138 citation statements)
references
References 25 publications
6
128
0
4
Order By: Relevance
“…They can detect glutamate dehydrogenase (GDH) (so-called common antigen) and/or major toxins A and B and are inexpensive, rapid, and easy to perform. A drawback of EIA toxin tests is a lack of sensitivity (8,9,13,15,16,20,22,27,30,32). Conversely, EIA GDH tests have good sensitivity but lack specificity, as they cannot distinguish toxigenic from nontoxigenic C. difficile (8, 13, 15, 23-25, 30, 32).…”
mentioning
confidence: 99%
“…They can detect glutamate dehydrogenase (GDH) (so-called common antigen) and/or major toxins A and B and are inexpensive, rapid, and easy to perform. A drawback of EIA toxin tests is a lack of sensitivity (8,9,13,15,16,20,22,27,30,32). Conversely, EIA GDH tests have good sensitivity but lack specificity, as they cannot distinguish toxigenic from nontoxigenic C. difficile (8, 13, 15, 23-25, 30, 32).…”
mentioning
confidence: 99%
“…1,45 Because GDH assays are purported to be highly sensitive but not specific for toxin-producing C. difficile isolates, this assay is usually used to screen stool specimens as part of a two-or three-step algorithm. Data from recent studies 46,47 supported the use of a two-step approach, although another study 7 raised concerns about using EIA tests for toxins A and B as confirmatory tests for GDH-positive samples because of the low sensitivity of the toxin EIAs. The SHEA-IDSA guidelines recommend screening liquid stools using a GDH EIA test and confirming positive results with either CCCN or toxigenic culture.…”
Section: Gdh Assaysmentioning
confidence: 99%
“…The EIA for toxin A/B has been adopted by most clinical laboratories because it is fast, convenient and inexpensive. Recent studies have shown however, that the sensitivity can be as low as 38% [55] . The EIA requires 100-1000 picograms of toxin as compared to the ability of the CCCNA to detect less than 10 picograms of toxin [53] .…”
Section: Laboratory Diagnosis Of CDImentioning
confidence: 99%